2020
DOI: 10.3390/ijerph17217825
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Pro-Inflammatory and Anti-Inflammatory Agents for the Suppression of Intimal Hyperplasia: An Evidence-Based Review

Abstract: Anti-atherogenic therapy is crucial in halting the progression of inflammation-induced intimal hyperplasia. The aim of this concise review was to methodically assess the recent findings of the different approaches, mainly on the recruitment of chemokines and/or cytokine and its effects in combating the intimal hyperplasia caused by various risk factors. Pubmed and Scopus databases were searched, followed by article selection based on pre-set inclusion and exclusion criteria. The combination of keywords used we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 69 publications
0
9
0
Order By: Relevance
“…As far as smooth muscle was concerned, most of the data are related to lung and vascular diseases. In fact, many experimental data showed that vascular smooth muscle cells are involved, together with endothelial cells, in the development of atherosclerosis, a pathology characterized by persistent inflammation and oxidative stress [ 150 ].…”
Section: Role Of Oxidative Stress In Gastrointestinal Muscular Altmentioning
confidence: 99%
“…As far as smooth muscle was concerned, most of the data are related to lung and vascular diseases. In fact, many experimental data showed that vascular smooth muscle cells are involved, together with endothelial cells, in the development of atherosclerosis, a pathology characterized by persistent inflammation and oxidative stress [ 150 ].…”
Section: Role Of Oxidative Stress In Gastrointestinal Muscular Altmentioning
confidence: 99%
“…Regardless of the type of foreign material or where it is placed in the body, the consequence of a FBR is the same: fibrotic hyperplasia, an important factor in the development of stenosis in tissues with implants ( Klopfleisch and Jung, 2017 ; Jeong et al, 2020 ). This explains why stenosis frequently occurs following ePTFE implantation, even among patients receiving anticoagulant therapy ( Che Man et al, 2020 ). Macrophages are key participants in the FBR caused by biomaterial implantation, and the macrophage phenotype can change in response to alterations of the microenvironment ( Chu et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Eventually, this event leads to high production of inflammatory cytokines and chemokines together with excessive release of the reactive oxygen species (ROS) and AGEs, thus activating the nuclear factor-κB (NFκB), activator protein-1 (AP-1), endothelin-1 (ET-1, a vasoconstrictive signal), pro-thrombotic tissue factors, and plasminogen activator inhibitor-1 (PAI-1) [ 100 , 101 , 102 ]. The increased levels of these molecules contribute to inflammation, vasoconstriction, and thrombosis [ 100 , 101 , 102 ]. Additionally, the presence of insulin resistance also contributes to greater ROS production [ 103 ].…”
Section: Cardiovascular Disease (Cvd) Complication In T2dmentioning
confidence: 99%